Strategi Komunikasi Corporate Social Responsibility di PT Pertamina (Persero) Region IV Wilayah Jawa Tengah dan DIY - Octaviana, Shoraya (Universitas Semarang, 2013)
Corporate social responsibility has become a global issue in the community and the company. CSR programs implemented by PT Pertamina (Persero) Region IV Regional Central Java and Yogyakarta in the areas of Education, Health, Environmental Conservation, Community Empowerment has been right on target. Corporate Social Responsibility program targeted, among others, so that more people know and use products - products Pertamina, as well as for good imaging Pertamina eyes of society. The communication strategy to the public (external strategies) used in the dissemination using print media such as newspapers and magazines nationally and locally. Electronic media using television and radio in Central Java and Yogyakarta as well as nationally. Communication strategies used in the dissemination to all employees of Pertamina, the media used in the form of intranet Pertamina, Energia magazine and TV Display. Theoretical basis used in this study is adopted from (Kottler, 2005) which states social initiatives of companies that can be taken for the implementation of CSR there are six forms of Cause Promotion, Cause Related Marketing, Corporate Social Marketing, Corporate Philanthropy, Community Volunteering and Socially Responsible Business Practices. The question in this research is how the Communication Strategy Corporate Social Responsibility (CSR) to PT Pertamina (Persero) Region IV Regional Central Java and Yogyakarta.